Comparison of strain generated in bone by "platform-switched" and "non-platform-switched" implants with straight and angulated abutments under vertical and angulated load: A finite element analysis study - Susan Paul; T V Padmanabhan; Shailee Swarup (Wolters Kluwer Medknow Publications, 2013)
Purpose: The aim of this study was to evaluate the microstrain exhibited by bone around immediately loaded, platform-switched, and non-platform-switched implants under vertical and angled loading using a finite element analysis (FEA) and also to evaluate whether platform-switched implants evoke a better response than non-platform-switched implants on a mechanical basis. Materials and Methods: Three-dimensional finite element study was undertaken to model and analyze an immediate loaded situation. FEA was chosen for this study since it is useful in determining the stress and strain around the dental implant. Bone responses to vertical and angulated loads on straight and angulated abutments (platform-switched and non-platform-switched abutments) were evaluated. Results: Non-platform-switched abutments tend to exhibit a lower tensile stress and compressive stress but higher microstrain value (conducive to higher chance of bone resorption) than platform-switched abutments. Ideal bone remodeling values of microstrain (50-3000 μϵ) were exhibited by platform-switched straight abutments under vertical load and angled load (with an abutment-implant diameter difference of 1 mm). Conclusion: In spite of the obvious advantages, the practice of immediate loading is limited due to apprehension associated with compromised bone response and a higher rate of bone loss around an immediately loaded implant. The mechanical basis for the concept of "platform switching" in immediately loaded situation is analyzed in this context. The results of this limited investigation indicated that the ideal values of microstrain (50-3000 microstrain) can be exhibited by platform switching of dental implants (with an abutment-implant diameter difference of 1 mm) and can be considered as a better alternative for prevention of crestal bone loss when compared to non-platform-switched implants.